Components of attack response inhibition in fencing - Gutiérrez-Davila, M.; Rojas, F. J.; Gutiérrez-Cruz, C.; Navarro, E. (European Journal of Sport Science, 2019)
Applying the Go/No-Go paradigm to fencing, we investigated the relationship between the moment at which the No-Go signal appeared after a movement had been initiated and the time required by fencers to suppress the motor execution of a step-lunge. Secondarily, we determined a time threshold from which movement inhibition results in an error. The No-Go stimulus was represented by a real attack movement. 18 elite fencers and a fencing master were included in the study. Four force plates measured the horizontal components of the fencer's and master's reaction forces, which were used to calculate the time components of the attack and the response inhibition process. Also, the velocity and displacement of the master's and fencer's respective centres of mass were estimated using inverse dynamics. In all cases, cognitive inhibition processes were completed after the onset of movement. Movement time was calculated using four time components (muscle activation, muscle deactivation, transition and braking time). The results obtained revealed that cognitive processes were not significantly affected by the timing of the appearance of the No-Go signal. In contrast, movement time and its time components tended to decrease when the time delay between the No-Go stimulus and the onset of the fencer's movement increased. In conclusion, any attempt to withhold an attack movement when it has already started leads to an error that increases the risk of being hit by the opponent, especially when attack is inhibited within 150 ms after the movement has started.